English immigrant voices : labourers' letters from Upper Canada in the 1830s - Cameron, Wendy; Maude, Mary McD; Haines, Sheila (CEL - Canadian Publishers Collection., 2000)
"This collection of letters opens new ground in Canadian social history - presenting a first-hand basis for Upper Canada's reputation as "a poor man's country." Editors Wendy Cameron, Sheila Haines, and Mary McDougall Maude confront the questions of authenticity that surround working-class letters of this early date, using their work on assisted emigration under the Petworth Emigration Committee to identify the writers and place their letters in the context of the emigration scheme that enabled them to come to Canada. Their letters, written or dictated to family and friends, provide a rare first-hand view of the immigrant experience from a working-class perspective."--Jacket